Plume Sample Modification at Icy Moons: Implications for Biosignatures - Pasek, Matthew A. (Frontiers in Astronomy and Space Sciences, 2020)
Water from the plumes of icy moons is a potential sampling target that may preserve the aqueous chemistry of the interior oceans, as well as organics and other biosignatures or prebiotic chemical precursors. Water within the plumes will be modified both as it is transported far above the moon's surface, and as samples are taken of the plume water. Plume water is found to freeze rapidly by evaporation and sublimation, increasing the concentration of solutes by a factor of 20%. Organics within samples of the plume water are also potentially subject to significant alteration as they are collected, particularly oxidation resulting from reaction with oxidants entrained on ejection in the plume or formed via breakdown of H2O on the surface as the drops are exposed in space. Mitigation of this oxidation will be critical to successful sample collection.